Kalimat Imperatif pada Naskah Pidato Pejabat Pemerintah DIY - Bherlian Tisofania; Sudaryanto (Belajar Bahasa: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research is chosen because the use of imperative sentences in the speech texts of DIY government officials is widely found. This research aims to find out and describe the types of imperative sentences found in the speeches of DIY government officials. The type of research used is descriptive qualitative with the method of listening and basic techniques of tapping and advanced techniques in the form of Simak Bebas Libat Cakap (SBLC) and note taking. For data analysis, the distributional method is applied with the basic technique of Direct Element Sharing and the advanced technique of lesap technique. The data validity technique in this research uses theoretical triangulation technique. The result of the research is that from 12 speech texts of DIY government officials, there are types of imperative sentences consisting of imperative invitation sentences as much as 11 data, such as let's, let's, invite, and come on and imperative hope sentences as much as 20 data, namely expect, expected, hope, expect, hope, hope, and hopefully.